Penampilan Agronomis dan Produktivitas Galur-Galur Padi Rawa di Lahan Lebak Bengkulu - Sumardi; Chozin, Mohammad; Sigit, Sudjatmiko (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2021)
Swamp rice breeding program offers a strategic value in optimizing the function of swamps as a source of food by means of providing high yield and adaptive rice varieties in swamp ecosystems. The aim of this study was to evaluate the agronomic performances and yield potential of 10 swamp rice lines. The experiment was carried out from June 2018 to November 2018 on shallow swampy land, Faculty of Agriculture, Bengkulu University, using a complete randomized block design with three replications. The swamp rice lines evaluated were UBPR 1, UBPR 2, UBPR 3, UBPR 4, UBPR 6, UBPR 7, UBPR 8, UBPR 9, UBPR 10, and UBPR 11 with Inpara 4 and Inpara 5 as the check varieties. The results showed that the 12 genotypes evaluated had significant variations in their agronomic performances and yield potential. UBPR 1, UBPR 3, UBPR 4, and UBPR 10 had relatively high plant postures and delayed maturity, but higher yield potentian, than the check varieties. UBPR 2, UBPR 7, and UBPR 8 showed comparable agronomic performances to the two comparison varieties, but higher in the yield potential. UBPR 4, UBPR 9, and UBPR 11 had agronomic performances and yield potential comparable to the check varieties